Pluronic F-127 Hydrogel for Delivering Antimicrobial Agents: A Bibliometric Analysis using Scopus Database - Khan Sharun; S. Amitha Banu; Sonu S. Nair; Rohit Kumar; A.M. Pawde; Kuldeep Dhama; Amar Pal (Journal of Pure and Applied Microbiology, 2023)
Infectious diseases caused by pathogenic microorganisms pose significant threats to public health globally. The emergence of antibiotic-resistant bacteria has further complicated the treatment of these infections, necessitating the exploration of alternative therapeutic strategies. Among these strategies, the use of hydrogels as delivery systems for delivering antimicrobial agents has gained considerable attention. This paper presents a comprehensive bibliometric analysis of the utilization of Pluronic F-127 (PF-127) hydrogel for delivering antimicrobial agents. The aim of this study is to explore the current research landscape, identify key trends, influential authors, and prominent journals in this field. The analysis is based on a systematic search conducted using the Scopus database. The analysis covered publication trends, geographic distribution, influential authors, and key journals in the field of PF-127 hydrogel-based antimicrobial agent delivery. The results revealed the growing interest in this field, with a focus on countries such as India, the United States, and Egypt. The analysis also identified top authors, institutions, and journals contributing to the research. The findings reveal the growth of research in this area, highlighting the potential of PF-127 hydrogel as a promising vehicle for antimicrobial agent delivery. It highlights the need for further research to optimize formulation parameters, explore combination therapies, conduct in vivo studies, and promote collaboration to maximize the therapeutic potential of PF-127 hydrogel-based delivery systems in combating infectious diseases and antimicrobial resistance. This paper provides valuable insights into the existing literature and serves as a reference for future research and development in the field.